SUPRACLAVICULAR BRACHIAL PLEXUS BLOCK WITH AND WITHOUT DEXAMETHASONE AS AN ADJUVANT TO LOCAL ANESTHETICS- AN OBSERVATIONAL STUDY. - Chinmay Sahu; K S Rao; Prasanna Mishra; Rajesh Panda (Student's Journal of Health Research, 2023)
Aim: Branchial plexus block accompanied by bupivacaine gives very efficacious anesthesia and analgesia. The addition of dexamethasone as an additive in bupivacaine prolonged the anesthetic and analgesic effect. This study aimed to contrast the outset and period of sensory and motor blockade and the period of the analgesic effect after adding dexamethasone to anesthesia and anesthesia without adding dexamethasone in the Supraclavicular branchial plexus block. Materials and Methods: This study included 100 patients and was conducted in Cuttack, Odisha. The age group of patients was between 20-60 years. Patients were divided into 2 categories:         Category 1 (cases): In this group, 16 ml of 2% lignocaine with adrenaline was administered and 16 ml of 0.5% bupivacaine with 10mg dexamethasone was administered.         Category 2 (control): In this group, 16 ml of 2% lignocaine with adrenaline was administered and 16 ml of 0.5% bupivacaine with saline was administered. Results: In Category 1 the sensory blockage was outset in 7 minutes whereas in Category 2 the outset of sensory blockage was 14 minutes. The motor blockage in Category 1 started in 4 minutes and in Category 2 it started in 19 minutes. There was no complication during the operative period and post-operatively. Conclusion: The addition of dexamethasone in 16 ml of 2 % lignocaine with adrenaline and 16 ml of 0.5% bupivacaine with 10mg dexamethasone increases the outset of sensory and motor blockage. It significantly increases the period of sensory and motor blockage and duration of analgesia. Recommendation: The in-plane approach is strongly recommended for this block; the needle tip and shaft should be continuously visualised in real-time to avoid inadvertent pleural puncture.